Implementasi Metode Steam Di Taman Kanak-kanak - Chintya Maharani; Zulminiati Zulminiati (Universitas Negeri Padang, 2021)
STEAM is important in AUD because the STEAM method is an active learning and triggers children to solve problems. So here can be achieved an effort to implement STEAM-Based Learning. So that many schools have used the STEAM method, one of which is Tiara Bunda Kindergarten, here are some aspects of development that have been developed using this STEAM method, for that the author is interested in exploring and analyzing the process of implementing the STEAM method in Tiara Bunda Kindergarten. The research method used in this research is descriptive qualitative. This research was conducted at Tiara Bunda Pesisir Selatan Kindergarten. Informants or respondents in this study were the Principal and Teachers. Data collection techniques were carried out through observation, interviews and documentation. The data obtained are described in accordance with the existing reality. Data analysis in the form of descriptions in the form of words and data validity techniques using data validity techniques using data reduction, data presentation, and drawing conclusions. The results of this study indicate that Tiara Bunda Pesisir Selatan Kindergarten has implemented or implemented learning using the STEAM method well. This can be seen from how the learning process takes place and the material provided is in accordance with the form of learning using the STEAM method, be it Science, Technology, Engineering, Arts, and Mathematics has been carried out properly and in accordance with the provisions